1996
DOI: 10.1128/jb.178.3.683-690.1996
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting mRNA processing and fimbrial biogenesis in the Escherichia coli pap operon

Abstract: The Escherichia coli pap genetic determinant includes 11 genes and encodes expression of Pap pili on the bacterial surface. An RNase E-dependent mRNA-processing event in the intercistronic papB-papA region results in the accumulation of a papA-gene-specific mRNA in considerable excess of the primary papB-papA mRNA transcription product. We have introduced mutations in the intercistronic region and studied the effect in vivo of these mutations on the processing event, PapA protein expression, and the biogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…However, it was evident that the activity of the pA promoter was very low and that most of the sfa transcription was initiated at pB under the conditions used (23). It was proposed previously that the sfaA transcript could be produced primarily by endoribonucleic processing of mRNA precursors that initiated at pB, similar to what was described in the transcriptional studies of the sfaA analog papA (1,24,26).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, it was evident that the activity of the pA promoter was very low and that most of the sfa transcription was initiated at pB under the conditions used (23). It was proposed previously that the sfaA transcript could be produced primarily by endoribonucleic processing of mRNA precursors that initiated at pB, similar to what was described in the transcriptional studies of the sfaA analog papA (1,24,26).…”
Section: Resultsmentioning
confidence: 60%
“…The high steady-state level of the sfaA transcript seems to be achieved by mechanisms similar to those described previously for other stable transcripts. For the gene analogous to sfaA, papA, it was determined that a stable transcript corresponding to only this gene is generated by RNase E-mediated cleavage at the intercistronic region between the papB and papA genes (24,26). Recently, it was demonstrated that the secondary structure of the resulting stable transcript after the RNase E cleavage includes a stemloop near the 5Ј end that stabilizes the transcript by protecting it from degradation (6).…”
Section: Discussionmentioning
confidence: 99%
“…Colonies of the pyelonephritis isolate E. coli J96 (Fig. 1A to C) were shown by flow cytometry to contain an average of 18% Ϯ 2% P-fimbriate bacteria labeled with a polyclonal anti-PapA antiserum (32). In E. coli CFT073, the positive proportion determined by flow cytometry was found to be 4.8% Ϯ 0.4% using an anti-P polyclonal serum (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…42,43) For example, suppression of mRNA degradation has been achieved by ribosome occupation due to enhancement of translation efficiency. 38,44,45) The introduction of hairpin structures into untranslated regions of mRNA, [46][47][48][49] removal of RNase recognition sequences, [50][51][52][53][54] and mutations of RNase 55) have been reported. A combinatorial approach employing these techniques to tune relative gene expression in an operon has been also reported.…”
Section: Discussionmentioning
confidence: 99%